2010
DOI: 10.3168/jds.2009-2507
|View full text |Cite
|
Sign up to set email alerts
|

Continuous lactation effects on mammary remodeling during late gestation and lactation in dairy goats

Abstract: The present study aimed to 1) elucidate whether continuous milking during late gestation in dairy goats negatively affects mammary remodeling and hence milk production in the subsequent lactation, and 2) identify the regulatory factors responsible for changes in cell turnover and angiogenesis in the continuously lactating mammary gland. Nine multiparous dairy goats were used. One udder half was dried off approximately 9 wk prepartum (normal lactation; NL), and the other udder half of the same goat was milked c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…It has been suggested that the milk yield of sows is influenced by various factors such as genotype, nutrition (Quesnel et al 2009), physical activity and sucking stimulation (Malmkvist et al 2012). During lactation, mammary epithelial cells undergo morphological and functional changes under the influence of hormones (such as prolactin) and many other factors [such as amino acid provision, blood flow, and endoplasmic reticulum stress (ERS)] (Noble and Hurley 1999;Baldi et al 2002;Boutinaud et al 2004;Rezaei et al 2013;Safayi et al 2010). The number of mammary cells and the amount of nutrients available to those mammary cells are the main determinants of milk production (Kim and Wu 2009).…”
Section: Introductionmentioning
confidence: 98%
“…It has been suggested that the milk yield of sows is influenced by various factors such as genotype, nutrition (Quesnel et al 2009), physical activity and sucking stimulation (Malmkvist et al 2012). During lactation, mammary epithelial cells undergo morphological and functional changes under the influence of hormones (such as prolactin) and many other factors [such as amino acid provision, blood flow, and endoplasmic reticulum stress (ERS)] (Noble and Hurley 1999;Baldi et al 2002;Boutinaud et al 2004;Rezaei et al 2013;Safayi et al 2010). The number of mammary cells and the amount of nutrients available to those mammary cells are the main determinants of milk production (Kim and Wu 2009).…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that differences can be observed in the level of oxidative stress with respect to the stages of lactation period 2,4 . The changes occurring at the composition of the milk in lactation period are resulted from the various factors such as epithelial cell proliferations, secretion activity, supplying of the nutrients and removing of the metabolic wastes by means of the blood 5,6 . General knowledge about oxidative stress relatedmetabolic disorders increases, and the pathologic effects of these disorders generally are associated with the free radical molecules [7][8][9] .…”
mentioning
confidence: 99%
“…Histomorphological features of poorly differentiated MEC can be observed by visualizing cellular morphology wherein the cells are smaller in size, absence of fat vacuole inside the cytoplasm and reduced cytoplasmic area. 17,18 In mammary carcinomas, aberrant expression of MUC1 was seen. MUC1 was located in the nuclei plus cytoplasm of majority of the MEC ( Figure 4C).…”
Section: Immunolocalization Of Muc1 and Ki67mentioning
confidence: 99%